Economic Performance Of Manufacturing Companies In Indonesia: Tangible Assets, It Capabilities, And Water Accounting - Arry Eksandy; Irma Paramita Sofia; Rudi Harianto; Farhan Ady Pratama; Riski Ulan Sari (Universitas Serang Raya, 2023)
This study aims to examine the effect of tangible assets, IT capabilities, and water accounting on the economic performance of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. Determination of the sample in this study using purposive sampling method. The research data in this study were obtained from audited annual financial reports, sustainability reports, and company performance summaries obtained from the Indonesian stock exchange website (www.idx.com) which were analyzed using a panel regression model. The results showed that tangible assets had a positive effect on economic performance, IT capabilities had no effect on economic performance and water accounting had no effect on economic performance